2017
DOI: 10.26719/2017.23.8.527
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among postmenopausal women in rural Minia, Egypt

Abstract: Qualité de vie parmi les femmes ménopausées dans les zones rurales du gouvernorat de Minya (Égypte)RÉSUMÉ La présente étude avait pour objectif de déterminer la prévalence et la sévérité des symptômes de la ménopause ainsi que leur impact sur la qualité de vie des femmes ménopausées dans les zones rurales du gouvernorat de Minya. Une étude transversale a été menée auprès de 1100 femmes ménopausées âgées de 45 à 60 ans sélectionnées par échantillonnage aléatoire à plusieurs degrés. L'échelle MRS (menopause rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…The author suggests that married women may have higher income and social support because they have a regular sexual life and have families for support. Furthermore, women with good family relations and positive partner support will experience less severe menopausal symptoms [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The author suggests that married women may have higher income and social support because they have a regular sexual life and have families for support. Furthermore, women with good family relations and positive partner support will experience less severe menopausal symptoms [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] 82.1% of Egyptian postmenopausal women above 40 years complained of joint and muscular discomfort, 69.6% physical and mental exhaustion, and 53.6% women complained of hot flushes as major symptoms in a study conducted by Nashwa N Kamal. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…This current study finding was contradictory on what has been reported by Waheed, Khanum, Butt, Ejaz, & Randhawa (2016) entitled 'Quality of Life after Menopause in Pakistani Women' that regarding Pakistani women who reported that the most common symptoms were lower back pain and vaginal dryness. Furthermore, most reported symptoms in the study by Kamal and Seedhom (2017) in rural Minia, Egypt"…”
Section: Figure (1)mentioning
confidence: 96%
“…Moreover, most of them were employment, more than two-thirds were married. Contradictory to a study in Egypt entitled ''Quality of life among postmenopausal women in rural Minia, Egypt'' carried by Kamal and Seedhom (2017), included 1100 Postmenopausal women aged 45-60 years had a mean age of 50.2 (SD 2.6) years. Most of the women were married, more than half were illiterate, majority of them were housewives and had children.…”
Section: Figure (1)mentioning
confidence: 99%